The ovine jugular vein as a model for interventional radiology procedures - Lu, Wei (Radiology and oncology (Ljubljana), 2008)
Background. Detailed knowledge of the ovine jugular vein anatomy and physiology is a prerequisite form proper use of sheep as teaching or an experimental model in interventional radiology. Material and methods. Ascending and descending jugular venograms in tilted position were done in 25 sheep to evaluate the jugular vein (JV) size and anatomy of its valves. Results. The average maximal diameter of 50 JVs was 13.34 1.18 mm. Each veincontained an average of 4.36 0.98 valves. All valves were competent and 96.3% were bicuspid. Conclusions. Because of similarities between ovine JV andhuman femoral vein in regards to diameters, number and type of valves and function of their valves with increased central and hydrostatic pressure, the ovine JV is a good model for evaluation of creation of JV valve incompetence, percutaneous valve transplantation and evaluation of prosthetic valve devices.
Keywords: anatomija; Anatomy And Histology; Bolezen, živalski modeli; Disease Models, Animal; Flebografija; Jugular Veins; Jugularne vene; modeli; Ovce; Phlebography; Radiografija intervencijska; Radiography, Interventional; radiologija; Sheep; vene; Venous Insufficiency; Venska insuficienca